PERANAN SEKTOR PERTANIAN PADAPEREKONOMIAN PROVINSI JAWATENGAH PERIODE 2000-2004 - Indah Widyarini; Any Suryantini; Suhatmini Hardyastuti (Agro Ekonomi, 2008)
This research aims to identify: (1) linkage between agricultural sectors towards Central Java economy; (2) agricultural sector contribution on added value increasing, especially for household income; and ·(3) what agricultural sector commodities are priorities on Central Java economy. The 2000 and 2004 input-output table of Central Java are analyzed by linkage analysis, output and income multiplier. The results show that agricultural sector growth in Central Java able to enhance any other sector activities. Tobacco, poultry, and its outputs are agricultural sector commodity which use a lot of any other economic sector outputs as its input. Then, sugar cane is agricultural sector output which is used as input by a lot of other economic sector. Central Java agricultural sector has role in increasing the added value, especially for household income. Agricultural sector commodities which have high rate of output multiplier are tobacco, poultry and its outputs. Central Java agricultural sector which becomes short term priority sector, has big investment impact toward total production increasing, and has role toward household income increasing are poultry and its outputs, tobacco, rubber,coffee, sugar cane and animal husbandry and its outputs. Furthermore, longterm priority sector, i.e. sectors which able to enhance any other sectoractivities, includes clove and any other plantation, agricultural services,wood, coffee, any other food substance and coconut.